A Study of the Subjective Probability Assessments necessary for the analysis of the Risk in Major Capital Investment Opportunities. - Hull, J. C. (Cranfield University, 1976)
Five case studies are analysed in depth and other investigations are carried out in order to answer questions concerned with: the nature of the distributions which are output from risk evaluation models. the important features of. the distributions which are input to risk evaluation models. the accuracy with which different methods for assessing subjective probability distributions are capable of providing the inputs to risk evaluation models. (iv) the way in which dependencies should be dealt with in risk evaluation models. and (v) the extent to which it is possible to distinguish important probability assessments from unimportant probability assessments in risk evaluation models.